1998
DOI: 10.1210/jcem.83.5.4807
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Perception of Stature, Acceptance of Therapy, and Psychosocial Functioning in Human Growth Hormone-Treated Girls with Turner’s Syndrome1

Abstract: This study evaluated the perception of stature, acceptance of therapy, and psychosocial functioning in relation to age at onset and time on treatment during 2 yr of GH therapy in 31 girls with Turner's syndrome grouped by age (group A: 3.7-5.8 yr, n = 9; group B: 7.2-11.8 yr, n = 13; group C: 12.5-16.4 yr, n = 9). The growth response after 2 yr was significant in the 3 groups when calculated in terms of growth norms for untreated Turner girls (mean increase in height SD score: +1.2, +1.5, and +1.1, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…This survey was not intended to become a consensus conference or issue guidelines but rather to evaluate and summarize common clinical practice in Europe and attitudes of pediatric endocrinologists in Europe. It is clear that while it is important to know about physicians’ attitudes, one should also know about the perception of height, acceptance of therapy and psychosocial functioning in the hypogonadal girls and their families in different populations [10, 11, 12, 13, 14]. Only few such surveys involving the patients themselves have been conducted [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This survey was not intended to become a consensus conference or issue guidelines but rather to evaluate and summarize common clinical practice in Europe and attitudes of pediatric endocrinologists in Europe. It is clear that while it is important to know about physicians’ attitudes, one should also know about the perception of height, acceptance of therapy and psychosocial functioning in the hypogonadal girls and their families in different populations [10, 11, 12, 13, 14]. Only few such surveys involving the patients themselves have been conducted [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that while it is important to know about physicians’ attitudes, one should also know about the perception of height, acceptance of therapy and psychosocial functioning in the hypogonadal girls and their families in different populations [10, 11, 12, 13, 14]. Only few such surveys involving the patients themselves have been conducted [11]. Adjustments of estrogen and growth hormone doses over time [10, 12]have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Among those studies that evaluated depressive symptoms via a validated questionnaire (Quality of Data Level 2) results were as follows: regarding symptoms severity, five studies (28% of subgroup) reported that individuals with TS had high severity depressive symptoms (Cunniff, Hassed, Hendon, & Rickert, 1995;Mao et al, 2015;Rickert et al, 1996;Rovet, 1993;Saad et al, 2014), 10 studies (56%) reported average severity symptoms (Chadwick, Smyth, & Liao, 2014;Freriks et al, 2015;Kiliç et al, 2005;Lagrou et al, 1998;McCauley, Ito, & Kay, 1986a;McCauley, Ross, Kushner, & Cutler, 1995;McCauley, Sybert, & Ehrhardt, 1986b;Ross et al, 1996;Rovet & Ireland, 1994;van Pareren et al, 2005), and three (17%) studies did not report data that were interpretable with regard to symptom severity (Lasaite, Lasiene, & Lasas, 2010;McCauley, Feuillan, Kushner, & Ross, 2001;Schmidt et al, 2006). Regarding symptom frequency, six studies (33%) demonstrated that subjects with TS were more frequently experiencing depressive symptoms as compared to those without TS (Chadwick et al, 2014;Kiliç et al, 2005;Lasaite et al, 2010;McCauley et al, 1986b;Saad et al, 2014;Schmidt et al, 2006), nine (50%) demonstrated an average frequency of symptoms (Cunniff et al, 1995;Freriks et al, 2015;Lagrou et al, 1998;McCauley et al, 1986aMcCauley et al, , 1995Rickert et al, 1996;Ross et al, 1996;Rovet & Ireland, 1994;van Pareren et al, 2005), one (6%) reported that individuals with TS were less frequently depressed than the i...…”
Section: Resultsmentioning
confidence: 99%
“…Overall, many subtypes of anxiety have been reported, including generalized anxiety, social anxiety, specific phobias, and obsessive-compulsive behaviors (Cardoso et al, 2004;El Abd, Patton, Turk, Hoey, & Howlin, 1999;Kilic et al, 2005;Moonga, Pinkhasov, & Singh, 2017). Despite many descriptive studies of anxiety and self-concept in TS (Kilic et al, 2005;Schmidt et al, 2006), a more precise breakdown of anxiety often results in conflicting information and may be affected by methodology including a reliance on self-report (Kilic et al, 2005;Lagrou et al, 1998). Because of the frequency of social anxiety in individuals with TS, it is important to consider that social desirability may be a confounding factor in the response pattern of self-report measures.…”
Section: Anxiety and Depression In Turner Syndromementioning
confidence: 99%